Pengaruh Kualitas Pelayanan dan Kepuasan Nasabah Terhadap Loyalitas Nasabah Mikro (Studi Kasus PT. Bank Rakyat Indonesia (Persero) Tbk Unit Sukajadi Bandung) - Ersha Faturochman; Ade Mubarok (Journal on Education, 2023)
Banking is one of the sectors of the economy that meets and serves its customers every day. The pros and cons of these financial institutions cannot be separated from the policies and treatment of employees to their customers. quality of service that makes customers feel satisfied and feel well served. The purpose of this study was to determine the effect of service quality and customer satisfaction on micro customer loyalty (Case Study of PT. Bank Rakyat Indonesia (Persero) Tbk Sukajadi Bandung Unit). The population in this study amounted to 101 people with non-probability sampling techniques and the type used was purposive sampling with a total of 30 people. This type of research is descriptive verification research. The statistical instrument used was regression analysis using validity, reliability, and normality tests. The results showed that service quality has a positive and significant effect on micro customer loyalty, customer satisfaction has an effect but not significant, while the analysis results of service quality and customer satisfaction on micro customer loyalty simultaneously have a positive and significant effect.